Magnetic actuator driver system for laser scanning capsule endoscopy - Kebapcioglu, Berkay; Erdil, Kuter; Erten, Ahmet Can; Ferhanoglu, Onur; Yelten, Mustafa Berke (Elsevier Gmbh, 2025)
This paper focuses on designing and implementing a power and area-efficient magnetic actuator driver interface integrated circuit for laser scanning capsule endoscopy. The proposed system contains a 3D-printed focus- adjusting actuator embarking a lens, multiple magnets, an external coil, battery, laser, and actuator driver integrated circuit with off-chip components. The actuator features multiple pantograph springs connected to the lens, as well as multiple magnets, enabling precise focusing capability through electromagnetic actuation. A magnetic actuator driver integrated circuit implemented in a commercial 180 nm CMOS process drives the coil at 32 Hz, which is the mechanical resonance frequency of the actuator. A novel control methodology for the driver has been devised, aimed at enhancing driving efficiency and mitigating total harmonic distortion. Simulations and measurements substantiate that the actuator can induce a 3.22 mm focal point displacement while the driver circuit delivers 9.62 mA (RMS) current to the 7.7 mH coil. Under these conditions, the system exhibits an aggregate power consumption of 11.48 mW, thereby achieving a power efficiency of 85.5%.
Keywords: Magnetic Actuator Driver; 3D Printed Focus Actuator; Amplitude And Harmonic Control; Capsule Endoscopy; Laser Scanning